Reassembling social work: six analytical territories to underpin the social project - Jiménez-Herrera, Julio (Cuadernos de Trabajo Social, 2025)
Frequently, we can observe that the professional intervention of social workers is expressed precisely and visibly at the level closest to the action as it is in a project and, often, assembled according to fixed components of that level of planning, namely: problem, objectives, goals, activities, resources, people responsible, etc. This article offers a proposal to reassemble the project and the intervention of Social Work at the planning level described above through analytical territories with the purpose of giving that theoretical/practical coherence in its structure and greater efficiency throughout. the acting process. As a result of the theoretical-reflective effort, five analytical territories are proposed that we believe underpin the intervention of the social worker. Among the main conclusions, derived from the investigative work, we can highlight the importance of the social worker considering these analytical territories when designing their projects to reinforce both the scheme (project) and the intervention itself.